Cannabinoids Inhibit Acid-Sensing Ion Channel Currents in Rat Dorsal Root Ganglion Neurons - Liu, Yu-Qiang; Qiu, Fang; Qiu, Chun-Yu; Cai, Qi; Zou, Pengcheng; Wu, Heming; Hu, Wang-Ping (PLOS ONE, 2012)
Local acidosis has been found in various pain-generating conditions such as inflammation and tissue injury. Cannabinoids exert a powerful inhibitory control over pain initiation via peripheral cognate receptors. However, the peripheral molecular targets responsible for the antinociceptive effects of cannabinoids are still poorly understood. Here, we have found that WIN55,212-2, a cannabinoid receptor agonist, inhibits the activity of native acid-sensing ion channels (ASICs) in rat dorsal root ganglion (DRG) neurons. WIN55,212-2 dose-dependently inhibited proton-gated currents mediated by ASICs. WIN55,212-2 shifted the proton concentration–response curve downwards, with an decrease of 48.6±3.7% in the maximum current response but with no significant change in the EC50 value. The inhibition of proton-gated current induced by WIN55,212-2 was almost completely blocked by the selective CB1 receptor antagonist AM 281, but not by the CB2 receptor antagonist AM630. Pretreatment of forskolin, an AC activator, and the addition of cAMP also reversed the inhibition of WIN55,212-2. Moreover, WIN55,212-2 altered acid-evoked excitability of rat DRG neurons and decreased the number of action potentials induced by acid stimuli. Finally, WIN55,212-2 attenuated nociceptive responses to injection of acetic acid in rats. These results suggest that WIN55,212-2 inhibits the activity of ASICs via CB1 receptor and cAMP dependent pathway in rat primary sensory neurons. Thus, cannabinoids can exert their analgesic action by interaction with ASICs in the primary afferent neurons, which was novel analgesic mechanism of cannabinoids.